2021
DOI: 10.1002/jid.3525
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved rice varieties on household food security in Northern Ghana: A doubly robust analysis

Abstract: This study determines the impact of the adoption of improved rice varieties on household food security using farm‐level data from 900 households in Northern Ghana. We employed the doubly robust inverse probability weighted regression adjustment procedure complementary with a propensity score matching approach on two indicators of food security (household dietary diversity score and subjective food security). Across all the various estimation procedures, we observed consistent positive effects of the adoption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…However, smallholder farmers have limited resources and the government may have to help them with subsidized fertilizer as well as other inputs such as agrochemicals to help them expand their rice production scale. That the respective technical efficiency scores for rice farmers from both agro-ecological regions are still far from the stochastic meta-frontier is an indication of the need of governments and other relevant authorities to provide necessary rice production-related information to help reduce the gap [52][53][54][55]. Information may be provided through farmer trainings with a focus on relevant rice technologies, especially with the technologies that fit the working environment of the lagging area (i.e., upland).…”
Section: Discussionmentioning
confidence: 99%
“…However, smallholder farmers have limited resources and the government may have to help them with subsidized fertilizer as well as other inputs such as agrochemicals to help them expand their rice production scale. That the respective technical efficiency scores for rice farmers from both agro-ecological regions are still far from the stochastic meta-frontier is an indication of the need of governments and other relevant authorities to provide necessary rice production-related information to help reduce the gap [52][53][54][55]. Information may be provided through farmer trainings with a focus on relevant rice technologies, especially with the technologies that fit the working environment of the lagging area (i.e., upland).…”
Section: Discussionmentioning
confidence: 99%
“…The AIPW model allowed for modeling both the treatment and the outcome such that if one was wrongly specified, the results would still be robust. Additionally, this method helped control selection bias at both the treatment and outcome levels (Lu et al, 2021). Regardless of these advantages over most impact assessment models, AIPW was less used among social scientists (Glynn & Quinn, 2010) and in particular, FBS impact studies.…”
Section: Methodsmentioning
confidence: 99%
“…To mitigate this drop, Qatar continued with its initiatives in sourcing seeds, fertilizers, agrochemicals, marketing, loans with reduced interest rates, guidance and support for farms from alternative countries, and greenhouse vegetable farming (Monroe 2020;Ben Hassen et al 2020). For other agricultural produce such as cereals-which are important for food security for many countries in Middle East and Africa (Ben Hassen et al 2020;Lu et al 2021;Miniaoui et al 2018)-we observed that India was the leading cereal exporter to Qatar accounting for 34.9 percent of the total cereal import value over the study period. It was followed by Pakistan and Australia at 25.9 and 11 percent respectively.…”
Section: Discussionmentioning
confidence: 99%